Histopathological outcomes of women with abnormal cervical cytology: A review of literature in Thailand - Kietpeerakool C. (Asian Pacific Organization for Cancer Prevention, 2014)
Cervical cytology remains the principal screening method to detect pre-invasive and invasive cervical lesions. Management of abnormal cervical cytology depends on the risk of encountering a significant cervical lesion or high-grade cervical disease. These risks may vary in different areas across the country. Thus, determining the rate of significant cervical lesion associated with each type of abnormal cervical cytology in each area is of critical importance for designing area-specific management approach. This review was conducted to evaluate the rate of high-grade cervical disease among Thai women with abnormal cervical cytology. A relatively high incidence of underlying significant lesions including invasive disease was demonstrated even in those having only minimal smear abnormality. This baseline information is crucial and must be taken into consideration in management of women with abnormal cytological screening to achieve the goals of comprehensive cervical cancer control in Thailand.